2017
DOI: 10.15171/hpp.2017.35
|View full text |Cite
|
Sign up to set email alerts
|

Physical fitness as an indicator of health status and its relationship to academic performance during the prepubertal period

Abstract: Background: Physical activity (PA) is considered one of the most important determinants of the health status in children, and predictor of morbidity/mortality in adults. The aim is to examine the relationship between physical fitness (PF), PA, obesity and academic performance (AP) in primary school children. Methods: Cross-sectional studies including 91 primary school students, aged 9 to 12 years, from the province of Córdoba. Data was collected from April to June 2014. We measured PF using part of the EUROFIT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Another strong predictor of future health is physical fitness, which has been defined as a set of attributes related to a person's ability to perform physical activities [10]. In the literature, cardiorespiratory fitness and muscular strength have been associated in children with cardiometabolic risk factors [11,12] and recently, cardiovascular fitness has been positively associated with academic performance [13]. Therefore, physical fitness, and in particular cardiorespiratory fitness, could modify the impact that body mass index (BMI) has on the risk of cardiovascular disease and obesity-related comorbidities, especially in children and adolescents [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Another strong predictor of future health is physical fitness, which has been defined as a set of attributes related to a person's ability to perform physical activities [10]. In the literature, cardiorespiratory fitness and muscular strength have been associated in children with cardiometabolic risk factors [11,12] and recently, cardiovascular fitness has been positively associated with academic performance [13]. Therefore, physical fitness, and in particular cardiorespiratory fitness, could modify the impact that body mass index (BMI) has on the risk of cardiovascular disease and obesity-related comorbidities, especially in children and adolescents [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Empirical evidence and systematic reviews have suggested a positive association between PF components and academic performance in children and adolescents [5][6][7][8][9]. For instance, Marques et al [10] have shown that there is a strong evidence for the association between CRF and academic performance which may be related to the positive effects of CRF on brain structure and cognitive functions [11].…”
Section: Introductionmentioning
confidence: 99%
“…Another factor to note, and that may be related to the low levels of achievement by students of both genders, is the poor physical condition of adolescents [ 30 , 31 ]. These deficiencies could influence the insufficient performance of the acrobatic movements analyzed.…”
Section: Discussionmentioning
confidence: 99%